Laparoscopic Adrenalectomy: 10-Year Experience, 67 Procedures - Simforoosh, Nasser; Soufi Majidpour, Heshmatollah; Basiri, Abbas; Ziaee, Seyyed Amir Mohsen; Behjati, Saeed; Mohammad Ali Beigi, Faramarz; Aminsharifi, Alireza (Urology Journal, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:right; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-bidi-language:FA; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Introduction: The purpose of this study was to evaluate the short-term and long-term results of laparoscopic adrenalectomies carried out in our center. Materials and Methods: A total of 67 laparoscopic adrenalectomies were performed during the 10 years between 1995 and 2005 at Shahid Labbafinejad Medical Center. A transperitoneal lateral approach was used in 65 (97.0%) of the patients, and retroperitoneal approach was used in 2 (3.0%). The clinical characteristics and the outcomes were reviewed in a retrospective study. Results: Indications for laparoscopic adrenalectomy in our patients were as follows: pheochromocytoma in 28 patients (41.8%), aldosterone-producing adenoma in 15 (22.4%), pseudocyst in 6 (9.0%), Cushing syndrome (macronodular adrenocortical hyperplasia) in 5 (7.5%), nonfunctioning adenoma (incidentaloma) in 5 (7.5%), myelolipoma in 2 (3.0%), almost normal adrenal tissue in 2 (3.0%), adrenal cyst in 2 (3.0%), adenocarcinoma in 1 (1.4%), and schwannoma in 1 (1.4%). The mean operative time for unilateral cases was 149.0 Â± 36.1 minutes. The mean intraoperative blood loss was 126 Â± 36 mL. Conversion rate to open surgery was 7.5%. Reoperation due to hemorrhage was performed in 1 patient. Conclusion: Laparoscopic adrenalectomy is a safe procedure in some adrenal tumors and a reasonable option for selected large adrenal tumors when complete resection is technically feasible and there is no evidence of local invasion.